2001
DOI: 10.1002/1521-3765(20011119)7:22<4913::aid-chem4913>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

(Phosphanyloxazoline)palladium Complexes, Part I: (η3-1,3-Dialkylallyl)(phosphanyloxazoline)palladium Complexes: X-Ray Crystallographic Studies, NMR Investigations, and Quantum-Chemical Calculations

Abstract: A series of systematically varied (eta3-1,3-dialkylallyl)palladium complexes of (4S)-[2-(2-diphenylphosphanyl)phenyl]-4,5-dihydrooxazole (PHOX) ligands were characterized by X-ray crystal structure analysis and NMR spectroscopy. Complexes with identical substituents in the 1,3-positions of the allyl group can form eight stereoisomers. In solution four to six isomers were observed and their conformations assigned with the aid of NOE experiments. The dynamic behavior of the complexes was analyzed. In addition, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(15 citation statements)
references
References 69 publications
(20 reference statements)
3
12
0
Order By: Relevance
“…However, we did find that a low solvent dielectric (in the 2–8 range) was important for obtaining high levels of enantioselectivity. Similar to other examples in the literature, 5254 we obtained an X-ray crystal structure of a Pd(allyl) + PF 6 − complex, 3 (see Fig. 1), and found that it was a competent catalyst for reactions of silyl enol ethers, suggesting that it is an intermediate in the reaction.…”
Section: Introductionsupporting
confidence: 82%
“…However, we did find that a low solvent dielectric (in the 2–8 range) was important for obtaining high levels of enantioselectivity. Similar to other examples in the literature, 5254 we obtained an X-ray crystal structure of a Pd(allyl) + PF 6 − complex, 3 (see Fig. 1), and found that it was a competent catalyst for reactions of silyl enol ethers, suggesting that it is an intermediate in the reaction.…”
Section: Introductionsupporting
confidence: 82%
“…The allyl group isomers 85 and 86 are in rapid equilibrium such that the nucleophile’s preferred attack ( 86 ), from the open quadrant at the allyl terminus trans to phosphorus, is nearly the exclusive reaction pathway. The resulting Pd 0 –olefin complexes (e.g., 87 ) have been observed by low temperature NMR spectroscopy 82a,b. Notably, stereoinduction in these alkylation reactions suffered if the steric bulk of the allyl substituents was reduced (e.g., 96 % ee for R= i Pr and 71 % ee for R=Me) 83.…”
Section: Resultsmentioning
confidence: 96%
“…15 Racemic substrates S1 – S7 were prepared as previously reported 38. [Pd(η 3 ‐1,3‐Ph 2 ‐C 3 H 3 )(μ‐Cl)] 2 ,39 [Pd(η 3 ‐1,3‐Me 2 ‐C 3 H 3 )(μ‐Cl)] 2 34a and [Pd(η 3 ‐cyclohexenyl)(μ‐Cl)] 2 40 were prepared as previously described. 1 H, 13 C{ 1 H}, and 31 P{ 1 H} NMR spectra were recorded using a 400 MHz spectrometer.…”
Section: Methodsmentioning
confidence: 99%